Adaptation of Malaysian retail design towards Omni – Channel and contextual retail concept / Muhammad Nadzrul Adam Mahusni and Maszura Abdul Ghafar - Muhammad Nadzrul Adam, Mahusni; Maszura, Abdul Ghafar (Universiti Teknologi MARA, Perak, 2018)
A new concept of Omni–Channel interactive retail design in Malaysia could revolutionize the Generation Y’s ( Gen Y) shopping experience. Studies found that the Gen Y’s culture and behaviour is the key to their changes in their shopping nature. The study is to identify how the amalgamation of the Omni–Channel shopping concept with fashion retail design could provide the ultimate shopping experience for Gen Y. This desktop study recommends an interactive retail’s cum Omni– channel space programming in creating an interactive retail design typology. It would benefit designers implementing successful retail design whilst catering current consumers shopping needs especially in Malaysia.